2021
DOI: 10.3892/ol.2021.12492
|View full text |Cite|
|
Sign up to set email alerts
|

GATA3 is downregulated in HCC and accelerates HCC aggressiveness by transcriptionally inhibiting slug expression

Abstract: Previous studies have reported that GATA3 is downregulated in multiple types of tumours, including gastric cancer and osteosarcoma. The aim of this study was to explore whether GATA3 serves as a tumour suppressor to inhibit hepatocellular carcinoma (HCC) development. Tumour tissue specimens and adjacent normal tissue specimens were obtained from 162 patients diagnosed with HCC in the Affiliated Hospital of Shaoxing University from July 2000 to May 2018. The result of the present study demonstrated that GATA3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These ndings are in line with the study by Zhang et al [9] who found that higher GATA3 immunoexpression was associated with low-grade bladder cancer. Zhang et al [17] made a similar observation in a study following up patients with hepatocellular carcinoma (HCC), in which lower GATA3 expression was associated with a poor prognosis. The authors suggested that overexpression of GATA3 decreased the proliferative, migratory and invasive capacity of HCC cell lines, while inhibition of GATA3 stimulated proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 67%
“…These ndings are in line with the study by Zhang et al [9] who found that higher GATA3 immunoexpression was associated with low-grade bladder cancer. Zhang et al [17] made a similar observation in a study following up patients with hepatocellular carcinoma (HCC), in which lower GATA3 expression was associated with a poor prognosis. The authors suggested that overexpression of GATA3 decreased the proliferative, migratory and invasive capacity of HCC cell lines, while inhibition of GATA3 stimulated proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 67%